ANALISIS ANGGARAN RESPONSIF GENDER PADA APBD KOTA SEMARANG TAHUN 2010-2013 - PUJI ASTUTI (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
Abstract Gender-responsive budgeting is an approach to integrate a kind of program for achieving gender equity and gender equality by budget intervention. This approach should be embraced by local governments through the application of gender perspective to identify processes, resources and institutional mechanisms. In accordance, this research aims to identify and comprehend the implementation of gender-responsive budgeting in Semarang Municipal during the fiscal years of 2010-2013. Using a descriptive-qualitative approach with the study of secondary data as a collecting data technique, this research showed the findings as follows: (1) there is a local regulation enacted to implement gender-responsive budgeting to all local government institutions (SKPD) within Semarang Municipal (2) there are many programs to improve and accelerate gender equality but the budget allocation still not reflected gender-responsive budgeting yet; especially in terms of transforming gender commitment as a local fiscal innovation.Keywords : Gender Mainstreaming, Gender-responsive Budgeting, Fiscal Innovation